Impact of coppicing on microclimate and understorey vegetation diversity in an ancient Mediterranean oak forest - Santi, Ilaria; Carrari, Elisa; De Frenne, Pieter; Valerio, Mercedes; Gasperini, Cristina; Cabrucci, Marco; Selvi, Federico (The Science of the total environment, 2024)
Coppicing is one of the oldest silvicultural practices and is still widely applied to produce renewable energy from broadleaf forests. However, the consequences on microclimate and understorey vegetation are still poorly understood, especially in Mediterranean oak forests. With the ongoing changes in the climate system and global biodiversity loss, a better understanding of how the forest temperature buffering capacity and below-canopy plant community are impacted by coppicing is crucial. Here we quantify microclimate and understorey vegetation changes in adjacent ancient coppice-with-standards and high forest stands dominated by oaks in Italy, where these systems have been applied for a long time. Air and soil temperatures were recorded for 2.5 years, and nested vegetation plots were used to analyse coppicing effects on species composition, taxonomic, phylogenetic, and functional diversity. Coppicing significantly reduced the forest temperature buffering capacity. The mean of the daily maximum temperatures over the entire period was 1.45 °C higher in the coppiced sites, whereas the mean of the daily minimum temperatures was 0.62 °C lower than in the high forest. Coppicing increased understorey species richness by favouring generalist taxa, but significantly decreased the proportion of forest specialists. The understorey community in coppiced forests consisted of more warm-adapted species. Moreover, coppicing also led to a loss of phylogenetic evenness and to shifts in diversity and community weighted mean Leaf Dry Matter content, pointing to habitat filtering and acclimation processes. In sum, we show that coppicing affects microclimate and understory vegetation in a direction that can exacerbate the effects of climate change, negatively affecting the oak forest specialist flora and its phylogenetic evenness.
Keywords: fylogeneze; Ecosystem; Mediterranean forest; Phylogenetic community structure; biodiverzita; Forests; Understorey; Microclimate; Quercus; dub (rod); Plant diversity; mikroklima; Coppice management; Biodiversity; lesy; Phylogeny; ekosystém